THE CONDITIONS AND MAIN RESULTS OF DEVELOPMENT OF INDUSTRIES OF FUEL AND ENERGY COMPLEX IN THE RESULTS OF FIRST STAGE OF IMPLEMENTATION OF THE ENERGY STRATEGY OF RUSSIA FOR THE PERIOD UP TO 2030 - V. Linnik; Y. Linnik (Вестник университета)
The article analyses the results of the first stage of the energy strategy of Rus-sia for the period up to 2030, as well as several reasons that significantly influenced the changes in the political situation in Russia and in the world, which led to the emergence of significant external and internal challenges that influenced the implementation of the strategy. The dynamics of development of oil and gas industry, oil refining, electric pow-er and gas-oil chemistry has considered. It has noted that in General, the implementa-tion of the Energy strategy until 2030 for the formation of oil and gas complexes in the Eastern regions of the country and the development of the hydrocarbon potential of the continental shelf of the Arctic seas and Northern territories of Russia within the frame-work of the implementation in 2017 has carried out successfully.